Immunohistohemical evidences of pregnancy in uterine curettage tissue by the use of a double immunocytochemical staining technique using cytokeratin 7 and vimentin antibodies - Trenkić Milan; Bašić Marin; Milentijević Maja; Petrović Aleksandar; Živković Vesna; Lazarević Viktor (Vojnosanitetski Pregled)
Background/Aim. Usual histopatological diagnosis of intrauterine pregnancy is made by demonstration of chorionic villi, but in the curettage tissue from intrauterine miscarriage they may not be present in all cases. The use of monoclonal antibody against cytokeratin as a sensitive and reliable marker for the morphologic discrimination between invasive trophoblastic (IT) cells and decidual cells has been well established. The aim of this study was to determine the presence of pregnancy in endometrial curettings when chorionic villi are absent from patients suspected of intrauterine pregnancy. Methods. Twenty cases of endometrial tissue specimens were investigated for cytokeratin and vimentin expression by a double immunostaining for detection of IT cells. Results. Out of the total number of cases (20) 17 cases expressed cytokeratin 7 positive IT cells, that are an evidence of pregnancy. Conclusion. The obtained results indicated, that double immunohistochemical demonstration of cytokeratin and vimentin is useful for identifying pregnancy in all chorionic villi-negative cases.